Pengaruh Keterlambatan Bagasi terhadap Kepuasan Penumpang Maskapai Batik Air di Bandar Udara Internasional Halim Perdanakusuma - Muhammad Dzaki Prayoga; Nur Makkie Perdana Kusuma (Sekolah Tinggi Teknologi Kedirgantaraan, 2026)
In aviation, Baggage delays caused by conveyor belt failures are one of the problems that may affect passenger satisfaction in air transportation services. This study aims to analyze the effect of baggage delays caused by conveyor belt failures on the satisfaction of Batik Air passengers at Halim Perdanakusuma International Airport, Jakarta. This study employed a quantitative approach using a survey method through questionnaires distributed to 100 respondents who experienced baggage delays due to conveyor belt failures. The sampling technique used was non-probability sampling with a purposive sampling method. The data were analyzed using simple linear regression, partial t-test, and coefficient of determination (R²). The results showed that baggage delays have a significant effect on passenger satisfaction with a significance value of 0.045 (< 0.05). The regression equation obtained was Y = 21.435 − 0.169X, indicating that the higher the baggage delay, the lower the passenger satisfaction. The coefficient of determination (R²) value of 0.548 indicates that baggage delays affect passenger satisfaction by 54.8%, while the remaining 45.2% is influenced by other factors outside this study. Therefore, baggage delays caused by conveyor belt failures have a significant effect on the satisfaction of Batik Air passengers at Halim Perdanakusuma International Airport, Jakarta.